(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objectives of this study were to determine the biofilm-forming capability and antimicrobial susceptibility of Escherichia coli recovered from bovine endometritis samples. Materials and Methods: A total of 120 uterine specimens were collected from cows suffering from endometritis for bacteriological examination. Antimicrobial susceptibility testing was carried out for all isolated E. coli by using the disc diffusion method. The isolates were phenotypically studied for biofilm-forming ability by cultivation on yeast extract -casamino acids Congo red agar (CRA). Some randomly selected isolates were chosen for the molecular identification of some virulence and resistance genes. Results: A total of 58(48.3%) E. coli isolates could be isolated from the 120 samples. Antimicrobial susceptibility testing exhibited that 91.4%, 79.3%, 79.3%, 74.1%, and 58.6% of the isolates were sensitive to gentamicin, amoxicillin-clavulanic acid, ciprofloxacin, cephalexin, and sulfamethoxazole-trimethoprim, respectively. On the other hand, 91.4% and 70.7% isolates were resistant to cefotaxime and doxycycline, respectively. Cultivation on CRA revealed that 46.6% of isolates were biofilm producers. The molecular detection of resistance and virulence genes declared that all isolates harbored blaTEM, sul1, tetA, qnrS, blaCTX-M, and fimH with a percentage of 100%, papC (40%), and hlyA (10%). FimH was the most prevalent biofilm-associated gene. Conclusion: The present study highlights the high prevalence of multi-drug- resistant E. coli associated with bovine endometritis. The detection of the fimH gene is circumstantial evidenced that this gene has a crucial role in biofilm formation in intrauterine pathogenic E. coli. J. Adv. Vet. Anim. Res., 7(3): 442-451, Sep 2020 http://doi.org/10.5455/javar.2020.g440